2010
DOI: 10.3174/ajnr.a2040
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome after Coil Embolization of Cavernous Sinus Arteriovenous Fistulas: Fig 1.

Abstract: BACKGROUND AND PURPOSE:Cranial nerve palsies are regularly observed in patients with arteriovenous fistulas of the cavernous sinus. The purpose of our study was to determine the long-term clinical outcome-with a special focus on extra-ocular muscular dysfunctions-in patients who had undergone endovascular treatment of a cavernous sinus fistula with detachable coils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Before proceeding with any treatment, careful assessment of a patient should be conducted, including clinical presentation; demographics; presence of comorbidities and their type, location, and classification; and the angiographic features of lesion 17 . Most previous investigations did not focus on neuroophthalmologic findings in detail or demonstrate the overall clinical outcome in patients after endovascular treatment of cDAVF 18 . The current study shows the efficacy and durability of endovascular embolization for cDAVF and significant regression of ophthalmologic involvement in a series of 46 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before proceeding with any treatment, careful assessment of a patient should be conducted, including clinical presentation; demographics; presence of comorbidities and their type, location, and classification; and the angiographic features of lesion 17 . Most previous investigations did not focus on neuroophthalmologic findings in detail or demonstrate the overall clinical outcome in patients after endovascular treatment of cDAVF 18 . The current study shows the efficacy and durability of endovascular embolization for cDAVF and significant regression of ophthalmologic involvement in a series of 46 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Bink et al, in an investigation of 19 cDAVF patients with ophthalmologic complications, demonstrated that endovascular treatment via the transvenous approach through the IPS with detachable coils led to durable angiographic cDAVF closure and effective relief of symptoms. However, there was a 44% rate of ophthalmologic signs in long-term follow-up 18 . Théaudin et al, in their study of endovascular treatment of dural carotid-cavernous fistulas, demonstrated that complete occlusion of the fistula was obtained in 87% of the patients treated via the transvenous approach, but only 25% of patients treated by the transarterial approach had the same outcome.…”
Section: Follow-upmentioning
confidence: 99%
“…Endovascular treatment of CCFs leads to closure of the fistula and resolution of symptoms and overall good long-term recovery. 2 The aim of our study was to review the experience of a tertiary referral hospital regarding clinical features, interventional treatment and outcome of 24 patients with CCFs, with emphasis on the impact of the disease, and its treatment, on vision.…”
Section: Introductionmentioning
confidence: 99%
“…(7) These permanent symptoms were associated with the space-occupying effect of the coil density in CS, and a coil volume of >200 mm3 was reported to be a critical factor. (7,8) Furthermore, dense packing of large areas of the CS includes not only the element of high cost for the amount of coils used but also difficulties in determining the optimal volume of coils. Therefore, as an alternative to dense CS packing, targeted coil embolization aimed at treating only the affected area is a reasonable strategy to reduce the number of coils used; in addition, morbidity rates are decreased by decreasing coil volume.…”
Section: Discussionmentioning
confidence: 99%